Operation Kinetic : Stabilizing Kosovo - Maloney, Sean M., 1967- (Potomac Books, An imprint of the University of Nebraska Press, 2018)
In the late 1990s, NATO led the Kosovo Force (KFOR), charged with stabilizing Kosovo and the former Yugoslav Republic of Macedonia after genocide and other atrocities were carried out in the Balkan region. Operation Kineticis not only a history of the origins and operations of the Kosovo Force but also a history of the vital operations conducted by the Canadian Army units and their allies assigned to KFOR during the crucial early days and months after entry into the province in 1999 and through 2000. Operating alongside American, British, French, Norwegian, Finnish, and Swedish forces, these surveillance and response units were instrumental in preventing violence in numerous areas before it could escalate and draw in the Serbian Army, which could have led to further genocide or war in the region. Sean M. Maloney, a Canadian military historian with extensive field experience in the Balkans, draws on numerous interviews and firsthand accounts of an operation that would later serve as a model in preparing for similar efforts in Afghanistan and provide a blueprint for stabilizing operations around the world.--